Pengaruh Return On Assets Dan Current Ratio Terhadap Kebijakan Deviden Pada Perusahaan Sektor Aneka Industri Di Bursa Efek Indonesia - Novi Fadhila; Nora Sipayung (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2021)
Return On Asset is a return from the management of investment and company assets, which is one of the indicators of profitability for the company with adequate measurement of the effectiveness of the entire company. Meanwhile, the current ratio is a reflection of the company's ability to pay off its current debt by looking at the condition of the company's current assets. The purpose of this study is to examine and analyze the effect of Return On Asset and Current Ratio on dividend policy in various industrial securities sector companies on the Indonesia Stock Exchange, either simultaneously or partially. The method used is quantitative associative, with purposive sampling technique, documentation technique and data analysis technique used is multiple linear regression. With the research results simultaneously, return on assets and current ratio do not affect dividend policy. Partially, return on assets has no effect on dividend policy, as well as current ratio to dividend policy.